The Regula as a Rhetorical Device in Roman Law - Tellegen-Couperus, Olga, (Early Modern History and Modern History E-Books Online, Collection 2024., 2025)
In this book, it is argued that twenty regulae in title D. 50.17 of Justinian's Digest are not the legal rules that scholarly wisdom has long held them to be, but are instead rhetorical arguments. As arguments, these regulae do not comfortably fit the modern perception of Roman law as a system and sometimes even appear to have no connection with law whatsoever. By explaining them in the context of rhetoric, and of Cicero's Topica especially, the authors identify and reconstruct the original tenor of these twenty regulae as well as that of the famous regula Catoniana , stating their case for a paradigm shift in the study of Roman law in the process. See Less